2010
DOI: 10.1001/archophthalmol.2009.386
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor in Retinoblastoma

Abstract: To investigate the immunohistochemical expression of vascular endothelial growth factor (VEGF) and to determine its possible association with tumor differentiation status, optic nerve and/or choroidal invasion, anterior chamber invasion, vitreous seeding, and basophilic staining of the vascular walls.Methods: A retrospective study was performed to identify the expression of VEGF in 47 of 129 consecutive patients with retinoblastoma treated at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…In vitro results further showed that HUVEC proliferation increased when co-cultured with Y-79 cells, an effect that was attenuated by aflibercept treatment. Angiogenesis in retinoblastoma plays an important role in tumor growth and local invasion, and the amount of angiogenesis in the retinoblastoma tumor has been suggested to be a prognostic factor [28, 29]. Therefore, aflibercept treatment could have therapeutic efficacy against retinoblastoma by reducing tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro results further showed that HUVEC proliferation increased when co-cultured with Y-79 cells, an effect that was attenuated by aflibercept treatment. Angiogenesis in retinoblastoma plays an important role in tumor growth and local invasion, and the amount of angiogenesis in the retinoblastoma tumor has been suggested to be a prognostic factor [28, 29]. Therefore, aflibercept treatment could have therapeutic efficacy against retinoblastoma by reducing tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that retinoblastoma cells express VEGF in hypoxic and normoxic conditions [29, 30, 58]. Moreover, HUVEC proliferation is increased by co-culture with Y-79 cells and reduced by bevacizumab treatment [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence VEGF-A represents one of the most powerful targets in antiangiogenesis therapy. Indeed in a retrospective study on several RB cases [14] was reported a positive correlation between VEGF-A staining intensity and different clinico-pathological markers of malignancy (mitotic and apoptotic indexes).…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Some studies have addressed the importance of VEGF in the development of retinal vasculature 26 and in survival of the newly formed retinal vessels. 27 Other studies 28 have found correlations between VEGF staining intensity and time to retinoblastoma progression and its mitotic and apoptotic indexes. Although these studies described VEGF expression in the tumor, they did not elaborate on its spatiotemporal expression or coexpression with other important angiogenic markers.…”
mentioning
confidence: 96%